2022
DOI: 10.1021/acssuschemeng.2c01703
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-Doped Manganese Oxide Catalyst for the Oxidative Coupling Synthesis of Fluorescent 2-Amino-1,9-dimethyl-3H-phenoxazin-3-one Using Atmospheric Oxygen

Abstract: The heterogeneous catalytic oxidative coupling synthesis of 2-amino-3H-phenoxazin-3-one (APXO) from the oxidative coupling of 2-aminophenol has important practical significance, due to its significant antiproliferative properties. However, the use of noble metals, alkaline additives, and explosive H 2 O 2 seriously restricts its applicability in industrial settings. Herein, through preparing a cerium-doped manganese oxide catalyst, we achieved the green synthesis of APXOs, using atmospheric oxygen as an oxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The excessive H 2 consumption at high temperatures could be attributed to the hydrogen spillover 15,45 and the surface oxygen reduction of ceria. 51,52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive H 2 consumption at high temperatures could be attributed to the hydrogen spillover 15,45 and the surface oxygen reduction of ceria. 51,52…”
Section: Resultsmentioning
confidence: 99%
“…The excessive H 2 consumption at high temperatures could be attributed to the hydrogen spillover 15,45 and the surface oxygen reduction of ceria. 51,52 The Pd valence state in Pd-based Ni foam reactors was explored by XPS (Fig. 5(a)).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Ce is also believed to have the ability to improve the distribution and concentration of the acidic site in metal oxide catalysts. 30 Building on the work of our group on Fe 2 O 3 -based 31,32 and CeO 2 -based 33,34 catalysts, atomically dispersed Ce-doped α-Fe 2 O 3 were synthesized through a simple co-precipitate method, which allowed the efficient reduction of aromatic nitro compounds using stoichiometric hydrazine hydrate at room temperature. A thorough characterization showed that the enhanced Lewis acidity of the host α-Fe 2 O 3 is a result of doping Ce atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Importantly, the VB and CB of CdS are 1.81 eV and −0.47 eV, respectively, 40 which are higher than those of CeO 2 (2.51 and −0.37 eV). 41,42 Inspired by these, and according to our research foundation in the thermocatalytic synthesis of imines 26,−28,43 and ceria-based (photo)catalyst, 44,45 we have successfully prepared cerium dioxide-modified cadmium sulfide photocatalysts in this work. Under visible light irradiation at room temperature, CdS/CeO 2 -200 °C enables atom-economic photocatalysis of the oxidative coupling of alcohols and amines to imines.…”
Section: ■ Introductionmentioning
confidence: 99%